A Healthy Diet Is Associated with Less Endothelial Dysfunction and Less Low-Grade Inflammation over a 7-Year Period in Adults at Risk of Cardiovascular Disease. Issue 3 (31st December 2014) - van Bussel, Bas CT; Henry, Ronald MA; Ferreira, Isabel; van Greevenbroek, Marleen MJ; van der Kallen, Carla JH; Twisk, Jos WR; Feskens, Edith JM; Schalkwijk, Casper G; Stehouwer, Coen DA
Abstract: Background: A healthy diet rich in fish, fruit, and vegetables, but moderate in alcohol and low in dairy products and meat, has been associated with a lower rate of incident cardiovascular disease (CVD). The underlying mechanisms, however, remain unclear. Endothelial dysfunction and low-grade inflammation play important roles in CVD. A healthy diet might modify these phenomena. Objective: We investigated the associations between the above food groups and overall biomarker scores of endothelial dysfunction and low-grade inflammation in a 7-y longitudinal study. Methods: Using longitudinal data from 557 participants at increased CVD risk from the CODAM (Cohort on Diabetes and Atherosclerosis Maastricht) Study, we assessed diet intake by food-frequency questionnaire and measured plasma biomarkers of endothelial dysfunction [von Willebrand factor, soluble vascular cell adhesion molecule 1, soluble endothelial selectin, soluble thrombomodulin, soluble intercellular adhesion molecule 1 (sICAM-1)] and low-grade inflammation [C-reactive protein, serum amyloid A, interleukin (IL)-6, IL-8, tumor necrosis factor α, and sICAM-1]. At baseline, participants were aged 59.6 ± 6.9 y. Measurements were performed then and after 7 y. Biomarkers were combined into overall scores (sum of z scores; higher scores indicating worse function). Longitudinal data were analyzed with generalized estimating equations and adjusted for sex, age, glucose metabolism, energy intake, body mass index, physical activity, alcohol consumption, and smoking. Results: Higher consumption of fish (per 100 g/wk), but not total consumption of vegetables, fruit, alcohol-containing beverages, dairy products, or meat, was associated with a lower overall endothelial dysfunction score over 7 y (β: −0.027; 95% CI: −0.051, −0.004). No associations were observed with the overall low-grade inflammation score. Further food component analyses indicated that consumption of more lean fish (per 100 g/wk) and raw vegetables (per 100 g/d), and fewer high-fat dairy products (per 100 g/d) was associated with less endothelial dysfunction [(β: −0.038; 95% CI: −0.072, −0.005), (β: −0.095; 95% CI: −0.191, 0.000), and (β: −0.070; 95% CI: −0.131, −0.009), respectively]. Consumption of more fresh fruit (per 100 g/d), wine (per 100 mL/wk), and poultry (per 100 g/d), and fewer high-fat dairy products (per 100 g/d) was associated with less low-grade inflammation [(β: −0.074; 95% CI: −0.133, −0.015), (β:−0.006; 95% CI: −0.013, 0.001), (β:−0.247; 95% CI: -0.479, -0.014), and (β:−0.100; 95% CI: −0.182, −0.019), respectively]. Conclusion: These data suggest that the dietary modification of endothelial dysfunction and low-grade inflammation, processes that are important in atherothrombosis, is possible.